Peru’s leadership in the Lima Group: emergence and failure (2015–2021) - Vidarte Arévalo, Oscar; Rivas Huerta, Andrea (Frontiers in Political Science, 2024)
This research seeks to understand the factors that enabled Peru, a medium-sized country in Latin America, to take on a leadership role in the creation and development of the Lima Group—a multilateral mechanism whose main objective was to find a resolution to the democratic crisis in Venezuela—as well as the subsequent failure of this leadership. Using the analytical tools provided by Neoclassical Realism, this study argues that Peru’s leadership was made possible not only by the growing importance of the Venezuelan crisis on the international agenda since 2015 but also by changes in regional and global power dynamics. These shifts allowed a country like Peru to exercise such leadership and garner greater interest from the United States. Additionally, the presence of a favorable domestic political climate and clear national interests led the Peruvian government to view this leadership as beneficial, not only for the region but also for Peru itself. However, despite the Venezuelan crisis remaining on the international agenda due to Nicolás Maduro’s continued hold on power, the hardening of the U.S. stance on Venezuela and political changes at the regional level since 2018 fractured the Lima Group and undermined Peru’s leadership. Moreover, domestically, political changes led to heightened instability, weakening Peru’s external position. Finally, the surge in Venezuelan migration and the onset of the COVID-19 pandemic shifted the priorities of Peru’s foreign policy, diminishing its focus on the Venezuelan crisis and contributing to the failure of its leadership.